An innovative flow cytometric approach for small-size platelet microparticles: Influence of calcium - Montoro-García, Silvia; Shantsila, Eduard; Orenes-Piñero, Esteban; Lozano, María Luisa; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2012)
Microparticles (MPs) are small submicron membrane-derived vesicles shed from a variety of cells and they have been implicated in different disorders. Accordingly, understanding of physiological characteristics of MPs and improvement of methods of their quantification are important for further advance in the field. Although flow cytometry is the most widely applied technique for MP analysis, it is limited by lack of adequate standardisation. Annexin V (AnV), which binds surface phos-phatidylserine (PS) with high affinity, has been long regarded as a marker of MPs, but AnV binding is Ca2+-dependent and it is unclear how [Ca2+] concentrations could affect AnV binding to MPs and its enumeration. MPs from citrated and heparinised plasma were labelled with AnV, anti-CD42b and quantified using an Apogee A50 flow cytometer. The small-size MP gate was defined with the use of size beads (from 0.1 to 0.5 μm) and confirmed with an in vitro assessment of platelet stimulation. Biotinylated anti-CD42b antibodies were then bound to streptavidin conjugated with different fluorochromes, leading to an amplified signal of platelet MPs (PMPs). Moderate increase of [Ca2+] concentrations in the annexin V staining buffer allows initial plasma recalcification and more accurate MP quantification in citrated plasma. Thrombin stimulation of platelet-free plasma containing only MPs did not produce any changes in the concentration of AnV+ MPs, but decreased the anti-CD42b binding. The results also indicate that prolonged storage and thrombin induce the release of AnV+ MPs whereas PS exposure in pre-existent MPs is not affected by thrombin. In conclusion, we present a sensitive protocol for the analysis of circulating and in vitro induced small-size PMPs that might contribute to future cardiovascular and clinical research.Note: The editorial process for this article was fully handled by Prof. Christian Weber, Editor-in-Chief.
Keywords: Small-size microparticles; annexin V; phosphatidylserine; calcium; streptavidin; flow cytometry